2015
DOI: 10.1039/c4cc08472a
|View full text |Cite
|
Sign up to set email alerts
|

A modular DNA origami-based enzyme cascade nanoreactor

Abstract: In this communication, we present a nanoscale reactor assembled from tuneable and spatially addressable tubular DNA origami units. We can controllably combine separate origami units equipped with glucose oxidase (GOx) and horseradish peroxidase (HRP), and demonstrate efficient GOx/HRP enzyme cascade reaction inside the tube. The reactor could be utilized as a nanoscale diagnostic tool, and modularity of the proposed system would further enable more complex reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
180
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(184 citation statements)
references
References 39 publications
2
180
0
2
Order By: Relevance
“…Linko et al 32. encapsulated GOx and HRP in DNA origami tubes with dimensions of 33 × 27 × 60 nm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Linko et al 32. encapsulated GOx and HRP in DNA origami tubes with dimensions of 33 × 27 × 60 nm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Fu et al [58] fabricated multienzyme cascades on DNA templates, where substrate channeling was realized using a DNA strand as a flexible swinging arm between the immobilized enzymes. Linko et al [59] showed how modular DNA origami building blocks could be assembled together to form a tubular enzyme cascade nanoreactor ( Figure 2C) for detecting glucose. The device could find use as a biosensor or a delivery vehicle for enzymatic payloads e.g.…”
Section: Smart Dna Nanodevices and Molecular Platformsmentioning
confidence: 99%
“…(B) A switchable tweezer-like enzymatic nanoreactor [57]. (C) A tubular DNA origami-based enzyme cascade nanoreactor for biosensing [59]. (D) A cargo mimic for dynein motor proteins [60].…”
Section: Shape-complementarity-based Constructionmentioning
confidence: 99%
“…Several attractive materials and successful strategies have been proposed leading to the design of an arsenal of multienzyme systems for mimicking the natural metabolic pathways in vitro. Examples are the preparations of hydrogels, 15,22 hourglass shaped nanochannel reactor, 23 mesoporous silica nanoparticles, 18,24 formation of inorganic nanocrystal-protein complexes 25 and self-assembled crystals, 26 microbeads, 27,28 DNA nanostructures, 4,5,11,[29][30][31] polymersomes, 14,32 nanoparticles, 33 nanobers, 13,16,34 graphene, 9,35 and metal-organic frameworks (MOFs). 17,36,37 In contrast to other scaffolds, MOFs, which are formed by the self-assembly of metal ions and organic linkers, feature ultrahigh surface area and porosity, uniform pores with tunable sizes, surfaces with variable chemistries, and structural diversity.…”
Section: Introductionmentioning
confidence: 99%